Productive performance of two phenotypes of free-range chickens in the Amazon region of Ecuador - Andrade–Yucailla, Verónica (2017)
The study was conducted at the Centro de Investigación  Posgrado y Conservación Amazónica (CIPCA), in the Poultry Program of the Universidad Estatal Amazónica, the objective of the research was to evaluate the effect of the phenotype of ﬁeld chicken on the behavior of the main productive parameters. We used 100 chickens of each phenotype, according to the plumage color (red and black) for the evaluation of the productive behavior we studied the initial and ﬁnal weight, weight gain, feed conversion, weight to the channel and yield to the channel, we applied a completely randomized design, for the analysis of the comparison of the means we used Tukey's 10th (1949) all data were analyzed in the statistical package Info Stat. In the three stages of development (initial, growth and fattening),  there were signiﬁcant  differences (P <0.001) between the treatments, obtaining  the best results in terms of gain of live weight 1260; 2120 and 1660 g, respectively, feed conversion (0.76, 1.77 and 3.28) treatment of the red phenotype and ﬁnal live weight (5080 g), which shows that the color of the plumage had inﬂuences on the bioproductive behavior of ﬁeld chicken, in which the red phenotype exceeded the black phenotype, cataloging it as a phenotype of excellence in meat production in the agro-meteorological conditions of the Amazon region of Ecuador.